Comparative Study Of The Tahlily Interpretation Method And The Muqaran Interpretation Method - Fita, Nofitayanti (Institut Agama Islam Sumatera Barat, 2025)
The purpose of this study is to analyze the comparison of the tahlily interpretation method and the muqaran interpretation method. This research uses a qualitative approach and a literature review method. Analytical methods or tahlily methods, namely, interpreting qur'anic verses by explaining all aspects contained in the interpreted verses and explaining the meanings included in them in accordance with the expertise and tendency of mufasir who interpret the verses. While Muqaran interpretation is one of the interpretive methods that use comparison techniques in revealing or explaining qur'anic verses, so that the main targets in this cashede are verses that seemto have similar redactions, which speak of the same case or two different cases , the second target is a verse that appears to contradict the hadith of the Prophet (peace be upon him) by birth, and the last is to compare the views of the scholars of the interpretation of the verse they interpreted.